Resonant cavity enhanced photoluminescence of tensile strained Ge/SiGe quantum wells on silicon-on-insulator substrate - 陈荔群 陈阳华 李成 (Optoelectronics letters, 2014)
The tensile strained Ge/SiGe multiple quantum wells （MQWs） grown on a silicon-on-insulator （SOI） substrate were fabricated successfully by ultra-high chemical vapor deposition. Room temperature direct band photoluminescence from Ge quantum wells on SOI substrate is strongly modulated by Fabry-Perot cavity formed between the surface of Ge and the interface of buried SiO2. The photoluminescence peak intensity at 1.58 μm is enhanced by about 21 times compared with that from the Ge/SiGe quantum wells on Si substrate, and the full width at half maximum （FWHM） is significantly reduced. It is suggested that tensile strained Ge/SiGe multiple quantum wells are one of the promising materials for Si-based microcavity lijzht emitting devices.